2000
DOI: 10.1038/sj.bjp.0703105
|View full text |Cite
|
Sign up to set email alerts
|

The group II metabotropic glutamate receptor agonist, DCG‐IV, alleviates akinesia following intranigral or intraventricular administration in the reserpine‐treated rat

Abstract: 1 This study examined whether activation of group II metabotropic glutamate (mGlu) receptors in the substantia nigra pars reticulata (SNr) could reverse akinesia in a rodent model of Parkinson's disease (PD). 2 Male Sprague Dawley rats, stereotaxically cannulated above either the SNr or third ventricle, were rendered akinetic by injection of reserpine (5 mg kg 71 s.c.). Eighteen hours later, the rotational behaviour induced by unilateral injection of the group II mGlu receptor agonist, (2S,2'R,3'R)-2-(2',3'-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 21 publications
1
37
0
Order By: Relevance
“…For instance, a recent study investigating the anti-parkinsonian potential of group III mGlu receptors found that DCPG could significantly reverse akinesia in reserpine-treated rats, but that this effect could not be blocked by a broad spectrum group III mGlu receptor antagonist (Broadstock et al, 2011). Given that group II mGlu receptor agonists have also been shown to alleviate akinesia in the same model of Parkinson's disease (Dawson et al, 2000), it therefore seems possible that the DCPG effects observed in the former study were mediated by mGlu2 receptors.…”
Section: Discussionmentioning
confidence: 95%
“…For instance, a recent study investigating the anti-parkinsonian potential of group III mGlu receptors found that DCPG could significantly reverse akinesia in reserpine-treated rats, but that this effect could not be blocked by a broad spectrum group III mGlu receptor antagonist (Broadstock et al, 2011). Given that group II mGlu receptor agonists have also been shown to alleviate akinesia in the same model of Parkinson's disease (Dawson et al, 2000), it therefore seems possible that the DCPG effects observed in the former study were mediated by mGlu2 receptors.…”
Section: Discussionmentioning
confidence: 95%
“…Systemic or intrastriatal administration of group I mGluR (subtypes 1 and 5) antagonists reversed catalepsy induced by a DA receptor blockade or DA depletion (Konieczny et al, 1998;Dawson et al, 2000;Ossowska et al, 2001). In unilateral and bilateral 6-OHDA models of PD, a chronic but not acute treatment with MPEP induced ipsilateral circling behavior and produced a full recovery of akinesia in the RT task (Spooren et al, 2000;Breysse et al, 2002).…”
Section: Metabotropic Glutamate 5 Receptors Antagonism As Anti-parkinmentioning
confidence: 96%
“…Pharmacological activation of mGlu2/3 receptors is also protective, whereas mGlu2/3 receptor blockade amplifies MPTP neurotoxicity (Matarredona et al, 2001;Battaglia et al, 2003). These findings are interesting because mGlu5 receptor antagonists and mGlu2/3 receptor agonists improve motor symptoms in experimental animal models of parkinsonism (Konieczny et al, 1998;Dawson et al, 2000;Kronthaler and Schmidt, 2000;Wolfarth et al, 2000;Lorenc-Koci et al, 2001;Breysse et al, 2002). We decided to examine the role of mGlu4 receptors in MPTP toxicity because these receptors are one the most promising targets for symptomatic drugs in experimental parkinsonism.…”
Section: Discussionmentioning
confidence: 99%